Application of Amelioran Compost of Empty Palm Plus Fruit Bunches to Soybean Plants in Ultisols through Multivariate Tests and Principal Component Analysis - A. Haitami; Seprido Seprido; Nariman Hadi; Andi Alatas (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
The decline in national soy output results from a decline in planted area. Optimizing ultisol land is one of the efforts undertaken to increase national soybean production. This study seeks to examine the effect of composting empty palm oil bunches on the growth and yield of soybeans using multivariate tests and principal component analysis during the compost's incubation period. The application of compost and empty palm fruit clusters was able to chelate Al-DD and increase the soil's available P and K. There is a positive Pearson correlation between pH, Ca, K, and Mg, as well as a positive Pearson correlation between all observed growth and development parameters of soybean plants. Pearson's correlation demonstrates the relationship between the characteristics of plant height, number of leaves, number of branches, number of pods, age of blossoming, age of harvest, and productivity. Positive correlations are observed for each parameter observed.